Hypokalemia in hospitalized patients in tertiary care teaching hospital Belagavi, Karnataka, India: a retrospective study - Lokapur, Anand; Badiger, Raju; Somannavar, Manjunath (International Journal of Research in Medical Sciences, 2017)
Background: Hypokalemia is well known condition in which serum potassium levels falls less than the normal level (normal range 3.5 to 5.1mmol/L). It has adverse effect on cardiac rhythm, blood pressure.1 The objective of the study was to look for causes and associated factors of hypokalemia. Methods: Patients age, sex, potassium value and primary diagnosis of hypokalemia patients collected from tertiary care teaching hospital retrospectively. Hypokalemia patients are classified based on the severity of hypokalemia, age, sex and primary diagnosis. Results: Study reveals that both males and females are equally affected by hypokalemia, individuals with age between 40 to 60 are most affected and less than 20 are least affected by hypokalemia. Conclusions: Hypokalemia is significantly associated with gastrointestinal and genitourinary disorders when compared with other disorders.